2016
DOI: 10.1021/acs.energyfuels.6b00640
|View full text |Cite
|
Sign up to set email alerts
|

Viscosity of Aged Bio-oils from Fast Pyrolysis of Beech Wood and Miscanthus: Shear Rate and Temperature Dependence

Abstract: ABSTRACT:The viscosity of four aged bio-oil samples was measured experimentally at various shear rates and temperatures by using a rotational viscometer. The experimental biooils were derived from fast pyrolysis of beech wood at 450, 500 and 550 °C, andMiscanthus at 500 °C (in this work, they were named as BW1, BW2, BW3 and MXG) in a bubbling fluidised bed reactor. The viscosity of all bio-oils kept constant at various shear rates at the same temperature, which indicated that they were Newtonian fluids.The vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…It is a significant physical property, as it essentially determines the flow characteristics of a fluid in a certain temperature and therefore affects the handling methods applied for storage and transportation etc. [7] The viscosity is also of great interest when the pyrolysis liquid is used as a component or an alternative to the binder in construction material, such as bio-bitumen, as it will affect the blending temperature of the mixtures. The viscosity of pyrolysis oils as produced can vary significantly; it is largely dependent on the type of feedstock and processing technology that results in the content of water and light fraction in the liquid [1].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a significant physical property, as it essentially determines the flow characteristics of a fluid in a certain temperature and therefore affects the handling methods applied for storage and transportation etc. [7] The viscosity is also of great interest when the pyrolysis liquid is used as a component or an alternative to the binder in construction material, such as bio-bitumen, as it will affect the blending temperature of the mixtures. The viscosity of pyrolysis oils as produced can vary significantly; it is largely dependent on the type of feedstock and processing technology that results in the content of water and light fraction in the liquid [1].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The results showed that the addition of bio-char (up to 20%) in pyrolysis oils could decrease the dynamic viscosity of the liquid in 40°C, but the liquid remained as a Newtonia n fluid. Cai et al [7] studied the rheology of four aged bio-oil samples from fast pyrolysis of miscanthus and beech wood at various shear rates and temperatures by using a rotational viscometer. All the pyrolysis oil samples maintained constant viscosity at various shear rates at the same temperature, which indicated their Newtonian characters.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Pyrolysis makes possible the use of low quality lignin-cellulosic material to produce not only bio-oils, but also gaseous fuels, and a carbonaceous rich solid phase, as reported in the literature . Studies include biomass pyrolysis [23,24,26,45,56,57,62,67,68], bio-oil chemical upgrading techniques [26,45,50], bio-oil physical-chemical properties [21,25,26,28,34,35,43,57,62,63], as well as separation and/or purification processes to improve bio-oil quality [17][18][19][20][21][22][30][31][32][33][36][37][38][39][40][41][46][47][48]51,53,54,[59][60][61]65,…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Depending on the processing temperature and atmosphere, these processes can be classified as pyrolysis, gasification and combustion. 3,4 Pyrolysis is the thermal decomposition in non-oxidizing environment, resulting in the production of a liquid, solid and gases, 5,6 and the yields of these products rely on the feedstock and processing conditions. 7,8 The combustion of solid fuels first undergo endothermic pyrolysis to produce combustible gases, which are subsequently combusted to supply heat required to produce further gases.…”
Section: Introductionmentioning
confidence: 99%